Risk Factor Analysis of Recurrent Acute Coronary Syndrome - Muhammad Aditya; Catharina Umbul Wahjuni; Muhammad Atoillah Isfandiari (Jurnal Berkala Epidemiologi, 2018)
Background: Acute coronary syndrome (ACS) is a form of life-threatening coronary heart disease. Interestingly, this entity has the possibility to recurrence with prevalence reaches 21-30% in a year. Purpose: This study aims to analyse risk factors associated with recurrent ACS incident. Methods: The analytic observation research with the case-control design was applied in this present study. Furthermore, this research was conducted at the Dr. Mohamad Soewandhie General Hospital, Surabaya. This study carried from February to July 2018. The samples used in this study cover 43 cases and 43 controls in the consecutive admission to the ACS patients who came to the cardiac clinic of the Dr. Mohamad Soewandhie General Hospital, Surabaya that meets the research criteria. On the other hand, bivariable analysis was performed using simple logistic regression and multivariable analysis was performed using multiple logistic regression. This study showed that the most influential risk factor for ACS recurrent. Results: incident were including control of Low-Density Lipoprotein Cholesterol (LDL-C) ≥ 100 mg/dL (p= 0.03; adjusted OR= 3.35; 95% CI= 1.16 < OR < 9.68), irregular exercise schedule (p < 0.01; adjusted OR= 9.15; 95% CI= 2.83 <OR <29.58), and smoking history (p= 0.02; adjusted OR= 4.07; 95% CI= 1.29 <OR <12.84). Conclusion: The control of LDL Cholesterol levels below 100 mg/dL, regular exercise, and avoid smoking are beneficial for people with ACS to reduce the risk of recurrent ACS incident.